2005
DOI: 10.1017/s0012162205001027
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the timed ‘Up & Go’ test in children

Abstract: The timed 'Up & Go' test (TUG) is a test of basic or functional mobility in adults which has rarely been used in children. Functional mobility was defined for this study as an individual's ability to manoeuvre his or her body capably and independently to accomplish everyday tasks. Reliability and validity of TUG scores were examined in 176 children without physical disabilities (94 males, 82 females; mean age 5y 9mo [SD 1y 8mo]; range 3 to 9y) and in 41 young people with physical disabilities due to cerebral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
250
2
30

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(300 citation statements)
references
References 22 publications
18
250
2
30
Order By: Relevance
“…The TUG test results also showed very high reliability, though it was slightly lower than the reliabilities of GMFM-88 and PEDI. Similar studies in the past showed the very high reliability of the TUG test for children with CP 12,16) and stroke patients 14,15) . On the contrary, KartzLeurer et al 18) found that the reliability of the TUG test for children with traumatic brain injury (ICC=0.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The TUG test results also showed very high reliability, though it was slightly lower than the reliabilities of GMFM-88 and PEDI. Similar studies in the past showed the very high reliability of the TUG test for children with CP 12,16) and stroke patients 14,15) . On the contrary, KartzLeurer et al 18) found that the reliability of the TUG test for children with traumatic brain injury (ICC=0.…”
Section: Discussionsupporting
confidence: 77%
“…Williams et al 12) examined the reliability of the TUG test in 176 healthy children (aged 3-9 years) and 41 children with CP (aged 3-9 years) and found that the reliability was excellent (ICC = 0. 99).…”
Section: Introductionmentioning
confidence: 99%
“…1 The literature is conflicting about the ability of the TUG to differentiate between the different GMFCS levels. 21,39 We found a significant difference in TUG values across these levels. Thus, we suggest that the TUG can give useful information about functional mobility in daily activities in comparable populations.…”
Section: Discussionmentioning
confidence: 64%
“…At the initial evaluation, the child presented lower score in relation to the highest score in the Berg scale in all of the assessed items. The TUG evaluation also showed a worse than expected performance for the age group (15 seconds), since the mean expected for children aged between three and nine years is 5.9 seconds (ranging from 3 to 13 seconds) 25 . Finally, posturography showed major body oscillation, demonstrating imbalance.…”
Section: Discussionmentioning
confidence: 72%